The risk of subsequent osteoporotic fractures is decreased in subjects experiencing fracture while on denosumab: results from the FREEDOM and FREEDOM Extension studies - Kendler, D. L. (Osteoporos Int, 2018)
SUMMARY: This post-hoc analysis queried whether women experiencing fracture on denosumab indicates inadequate treatment response or whether the risk of subsequent fracture remains low with continuing denosumab. Results showed that denosumab decreases the risk of subsequent fracture and fracture sustained while on denosumab is not necessarily indicative of inadequate treatment response. INTRODUCTION: This analysis assessed whether a fracture sustained during denosumab therapy indicates inadequate treatment response and if the risk of a subsequent fracture decreases with continuing denosumab treatment. METHODS: In FREEDOM, a clinical trial to evaluate the efficacy and safety of denosumab, postmenopausal women with osteoporosis were randomized to placebo or denosumab for 3 years. In the 7-year FREEDOM Extension, all participants were allocated to receive denosumab. Here we compare subsequent osteoporotic fracture rates between denosumab-treated subjects during FREEDOM or the Extension and placebo-treated subjects in FREEDOM. RESULTS: During FREEDOM, 438 placebo- and 272 denosumab-treated subjects had an osteoporotic fracture. Exposure-adjusted subject incidence per 100 subject-years was lower for denosumab (6.7) vs placebo (10.1). Combining all subjects on denosumab from FREEDOM and the Extension for up to 10 years (combined denosumab), 794 (13.7%) had an osteoporotic fracture while on denosumab. Of these, one or more subsequent fractures occurred in 144 (18.1%) subjects, with an exposure-adjusted incidence of 5.8 per 100 subject-years, similar to FREEDOM denosumab (6.7 per 100 subject-years) and lower than FREEDOM placebo (10.1 per 100 subject-years). Adjusting for prior fracture, the risk of having a subsequent on-study osteoporotic fracture was lower in the combined denosumab group vs placebo (hazard ratio [95% CI]: 0.59 [0.43–0.81]; P = 0.0012). CONCLUSIONS: These data demonstrate that denosumab decreases the risk of subsequent fracture and a fracture sustained while on denosumab is not necessarily indicative of inadequate treatment response. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00198-018-4687-2) contains supplementary material, which is available to authorized users.